Use Database to Evaluate the Prevalence of Hunger Among Adolescents in Brazil - Amorim, Ana Laura Benevenuto de; Ribeiro Junior, José Raimundo Sousa; Gonçalves, Helida Ventura Barbosa; Bandoni, Daniel Henrique (Frontiers in Nutrition, 2021)
The burden of food insecurity and malnutrition is a severe problem that affect many countries, in the last years Brazil has witnessed an increase in food insecurity and hunger. However, there is little available information and food security assessments are household measures, so the use of available databases is essential to expand the information and support decision-making in the fight against food security. This study aims to evaluate the relationship between reports of hunger among adolescents and its sociodemographic characteristics. We used data from the 2015 National School Health Survey (PeNSE). The main variable of interest was obtained from responses to the following question: “Over the past 30 days, how often have you gone hungry, because you did not have enough food at home?” The responses have been divided between those who reported going hungry and those who did not. Their socioeconomic characteristics were evaluated simultaneously. For the statistical analysis, we conducted the Pearson chi-squared test and multiple analyses using Poisson regression models. A total of 101,888 adolescent were evaluated. The variable use to measure a hungry was associated with maternal education, internet access and fruit intake. The results show there is a positive association between adolescents reported having gone hungry and sex, race, live in households with more than five people, those who do not live with their father, and those who have plans to work or do not know what they will do after finishing ninth grade. The results demonstrate that it is possible to use secondary data with a single question to assess and provide monitoring and insight into how food security impacts differently socio-demographic groups.